Obstetric fistula and related factors: assessing pattern and quality of life among women in Southwest Nigeria - Afolabi, Adebukunola O.; Bifarin, Mary T.; Oluwasanmi, Gladys O.; Oladokun, Munirat O.; Fatoke, Helen F.; Abioye, Abigail A.; Daramola, Lauretta S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Obstetric fistula remains major contributor to maternal morbidity in low resource countries. Study examined quality of life and related factors among women with obstetric fistula in Southwest Nigeria. Methods: A cross-sectional study, involving 159 purposively selected women receiving care at the fistula centre, Wesley Guild Hospital, Ilesa, Southwest Nigeria. An adopted interviewer-administered World Health Organization Quality of Life Scale, WHOQOL-BREF was employed to examine quality of life. Data was processed and analyzed using IBM statistical product and service solutions (SPSS) software version 25. Analysis was done at univariate, bivariate and multivariate levels. Fisher’s exact, Analysis of Variance, Independent t-test and Regression analysis examined association and significance, p<0.05. Results: Findings shows that 64.20% of the women had vesicovaginal fistula, 17.60% had rectovaginal fistula, 10.70% had uterovaginal fistula while 7.5% had ureterovaginal fistula. The mean scores for physical, psychological, social relationship and environmental health domains were 48.92 ±14.89, 39.91±17.42, 68.71±30.85, 42.75±18.60 respectively. Overall quality of life had mean score of 19.89 ±26.51 while 82.4% of the women had low quality of life, 2.5% had moderate and 15.1% had high quality of life overall. Regression analysis shows significant association between low quality of life and primipara (p=0.002, RRR=32.55, CI=3.73-284.19), multipara (p<0.001, RRR=23.20, CI=5.12-105.13), middle socio-economic status (p=0.02, RRR=4.62, CI=1.29-16.59). Conclusions: Significant proportion of the women studied had low quality of life. Parity and socio-economic status were main predictors of quality of life. Holistic management of obstetric fistula should take cognizance of these variables for optimal outcomes.